2022
DOI: 10.2337/db21-0443
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 Regulates the Interferon Signaling and Endoplasmic Reticulum Stress Response in Pancreatic β-Cells in Autoimmune Diabetes

Abstract: Type 1 diabetes (T1D) results from autoimmune destruction of β-cells in the pancreas. Protein tyrosine phosphatases (PTPs) are candidate genes for T1D and play a key role in autoimmune disease development and β-cell dysfunction. Here, we assessed the global protein and individual PTP profiles in the pancreas from early onset non-obese diabetic (NOD) mice treated with an anti-CD3 monoclonal antibody and interleukin-1 receptor antagonist. The treatment reversed hyperglycemia and we observed enhanced expression o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…The gene set enrichment analysis shows the significant upregulation of hallmark interferon gamma response genes, oxidative phosphorylation, and IL-6, JAK, and STAT3 signaling ( Figure 3 B–D) in the PTPN2 KO cells compared to WT, thereby verifying recent results showing the upregulation of interferon gamma signaling after PTPN2 knock down in different beta cell models [ 27 ].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The gene set enrichment analysis shows the significant upregulation of hallmark interferon gamma response genes, oxidative phosphorylation, and IL-6, JAK, and STAT3 signaling ( Figure 3 B–D) in the PTPN2 KO cells compared to WT, thereby verifying recent results showing the upregulation of interferon gamma signaling after PTPN2 knock down in different beta cell models [ 27 ].…”
Section: Resultssupporting
confidence: 83%
“…PTPN2 has also been shown to modulate IFN-γ signal transduction in the beta cell and regulate cytokine-induced apoptosis [ 26 ]. Functionally, PTPN2 deficiency has been shown to exacerbate type I and II interferon-signaling networks [ 27 ] and knockdown of PTPN2 in EndoC-βH1 human-beta-like cells demonstrates an amplification of an inflammatory response via STAT1 phosphorylation. We sought to build upon these findings by investigating the effects of a functional PTPN2 knockout in sBC using detailed phenotypic analyses and novel co-culture systems by employing autoreactive T cell transductants targeting sBC.…”
Section: Introductionmentioning
confidence: 99%
“…Downstream to STAT1 is the transcription factor IRF1, which has anti-inflammatory effects in β cells through the induction of SOCS1 ( Moore et al., 2011 ). SOCS1 and PTPN2 are negative regulators of cytokine signaling ( Chong et al., 2002 ; Elvira et al., 2022 ; Moore et al., 2009 ) and are both associated with T1D risk loci ( Onengut-Gumuscu et al., 2015 ; Ram and Morahan, 2017 ). Previous reports have shown that SOCS1 overexpression in NOD mice islets prevent diabetes ( Flodstrom-Tullberg et al., 2003 ), and delays allogeneic islet graft rejection in mouse models ( Solomon et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress activated by overstimulation mainly involves three unfolded protein-response signalling pathways, including activating transcription factor 6 (ATF6) pathway, double-stranded RNA-activated protein kinase (PKR)-like endoplasmic reticulum kinase (PERK) pathway, and inositol-requiring enzyme 1 (IRE1) pathway. While moderate ER stress can effectively protect the body, excessive ER stress causes degeneration [ 48 , 49 ]. Song X et al evidenced that ER causes apoptosis in PDL and vascular calcification in a rat model [ 50 ].…”
Section: Histological and Biochemical Changes In Ligaments Specifical...mentioning
confidence: 99%
“…In the previous study of Tan J et al, ER stress was also found to reduce the osteogenic differentiation ability of PDL when influenced by tumour necrosis factor-α [ 46 ]. Both indicate that an inflammatory microenvironment causes drastic interruption throughout the physiological functioning of cell mechanisms in ligaments [ 49 , 51 ].…”
Section: Histological and Biochemical Changes In Ligaments Specifical...mentioning
confidence: 99%